2004
DOI: 10.1017/s0022112004001156
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent flows in an emptying filling box

Abstract: We examine the transient buoyancy-driven flow in a ventilated filling box that is subject to a continuous supply of buoyancy. A rectangular box is considered and the buoyancy input is represented as a turbulent plume, or as multiple non-interacting plumes, rising from the floor. Openings in the base and top of the box link the interior environment with a quiescent exterior environment of constant and uniform density. A theoretical model is developed to predict, as functions of time, the density stratification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 10 publications
4
72
0
Order By: Relevance
“…Estimates of the interface thickness for the salt bath experiments of Kaye & Hunt (2004) predict an interface thickness in the range of 0.5-0.75 mm. While accurate measurement of this thickness was not possible during those experiments, laboratory images show the steady-state interface to be extremely sharp as can be observed, most especially, from figure 13 of Kaye and Hunt's paper.…”
Section: Comparison With Previous Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…Estimates of the interface thickness for the salt bath experiments of Kaye & Hunt (2004) predict an interface thickness in the range of 0.5-0.75 mm. While accurate measurement of this thickness was not possible during those experiments, laboratory images show the steady-state interface to be extremely sharp as can be observed, most especially, from figure 13 of Kaye and Hunt's paper.…”
Section: Comparison With Previous Analysesmentioning
confidence: 97%
“…The transient model for a single enclosure was presented by Kaye & Hunt (2004). They demonstrated that the time evolution is controlled by the magnitude of the emptying time…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the analysis was to determine both the variation in the volume of the upper layer, 1 V , (i.e. the change in position of the interface, h ), and the build-up of gas in the upper layer, c , during the transient part of the release and also their steady state values.…”
Section: Mathematical Model Of Gas Build-upmentioning
confidence: 99%
“…Following Kaye and Hunt [1] the rate of change of the volume of the upper layer can be expressed as:…”
Section: Mathematical Model Of Gas Build-upmentioning
confidence: 99%
“…Choosing the amplitude of environmental temperature variations T , the typical ventilation rate is q 0 = A * √ αgH T , giving the time for ventilation to affect the interior temperature as t 4 = V i /q 0 . This time scale is the analogue of the flushing time scale defined by Holford & Hunt (2000) (for a well-mixed space, with the temperature difference scale set by the initial conditions) or Kaye & Hunt (2004) (for a two-layer stratification, with the temperature difference scale set by plume dynamics). In both these earlier studies, the competition between a flushing time scale and a heating (Holford & Hunt 2000) or filling (Kaye & Hunt 2004) time scale was used to understand the dynamics of natural ventilation in an insulated space.…”
Section: Model Of a Naturally Ventilated Space With Internal Thermal mentioning
confidence: 99%